2011
DOI: 10.1007/s11816-011-0179-y
|View full text |Cite
|
Sign up to set email alerts
|

An easy and efficient protocol in the production of pflp transgenic banana against Fusarium wilt

Abstract: This study describes an efficient protocol for Agrobacterium tumefaciens-mediated transformation of two subgroups of genotype AAA bananas (Musa acuminata cv. Pei Chiao and Musa acuminata cv. Gros Michel). Instead of using suspension cells, cauliflower-like bud clumps, also known as multiple bud clumps (MBC), were induced from sucker buds on MS medium containing N 6 -Benzylaminopurine (BA), Thidiazuron (TDZ), and Paclobutrazol (PP333). Bud slices were co-cultivated with A. tumefaciens C58C1 or EHA105 that carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…For example, no results are available from race 1 field trials (Subramaniam et al, 2006;Paul et al, 2011;Ghag et al, 2012), and field results for TR4 tolerance are often absent (Hu et al, 2013;Mahdavi et al, 2012;Yip et al, 2011). In a single paper published 9 years ago, two of 51 Cavendish transformants that expressed the human lysozyme (HL) gene fruited in a TR4 field trial (Pei et al, 2005).…”
Section: Non-traditionalmentioning
confidence: 99%
“…For example, no results are available from race 1 field trials (Subramaniam et al, 2006;Paul et al, 2011;Ghag et al, 2012), and field results for TR4 tolerance are often absent (Hu et al, 2013;Mahdavi et al, 2012;Yip et al, 2011). In a single paper published 9 years ago, two of 51 Cavendish transformants that expressed the human lysozyme (HL) gene fruited in a TR4 field trial (Pei et al, 2005).…”
Section: Non-traditionalmentioning
confidence: 99%
“…Scientists around the world have investigated resistance breeding (Hwang and Ko 2004 ; Smith et al2006), chemical control (Nel et al 2007), biocontrol (Saravanan et al 2003; Cao et al2005; Lian et al2009) and molecular methods (Paul et al 2011; Yip et al 2011),in search of methods to control the disease. Some of these studies were found to effectively suppress Foc growth in the laboratory and in greenhouses, but were unable to efficiently control Fusarium wilt in the field.…”
Section: Introductionmentioning
confidence: 99%
“…However, the performance of the banana industry is affected by biotic and abiotic stresses such as Fusarium wilt (Czislowski et al 2018;Dale et al 2017), cold stress (Dou et al 2016), typhoon (Yu et al 2014). Most banana cultivars are triploid, with long generation times, and sterility, hence, it is difficult to cultivate new resistant banana germplasm by means of cross breeding (Ghag et al 2014;Tripathi et al 2008;Yip et al 2011). In addition, the selection and breeding of new varieties by screening mutants has certain randomness and requires longer periods of time (Hasan et al 2013).…”
Section: Introductionmentioning
confidence: 99%